The case against Diodore and Theodore: texts and their contexts - Behr, John (Oxford Early Christian Texts, 2011)
"[E]xtracts from the writings of Diodore and Theodore as cited by their opponents and supporters, in their historical order, from the death of Theodore to his condemnation at the Council of Constantinople in 553"--P. [vii]-viii